The Relationship between Executive Pay and Firm Performance in China: Evidence from Listed Companies in Jiangsu Province - Lu, YaoShu (2020)
This study examines the relationship between executive pay and firm performance and based it on tournament theory. Thus, it is necessary to research whether tournament theory is suitable in the context of China. This study adopts quantitative research, which is based on secondary data, and uses 100 listed companies in China Jiangsu province as examples to evaluate whether executive pay has relationship with firm performance. To further evaluate the influence of state ownership to this relationship, this study chooses 50 state-owned companies and 50 non-state-owned companies for comparative analysis and evaluate these data through SPSS to do further analysis. Through the research, it found that in line with the tournament theory, executive pay is positively related to the firm performance, and this relationship is significant correlation in non-state-owned companies. Meanwhile, this study found that pay gap is also related to executive pay and firm performance and includes limitations, and suggestions for future research.